Changes in T Cell and Dendritic Cell Phenotype from Mid to Late Pregnancy Are Indicative of a Shift from Immune Tolerance to Immune Activation - Shah, Nishel Mohan; Herasimtschuk, Anna A.; Boasso, Adriano; Benlahrech, Adel; Fuchs, Dietmar; Imami, Nesrina; Johnson, Mark R. (Frontiers in Immunology, 2017)
During pregnancy, the mother allows the immunologically distinct fetoplacental unit to develop and grow. Opinions are divided as to whether this represents a state of fetal-specific tolerance or of a generalized suppression of the maternal immune system. We hypothesized that antigen-specific T cell responses are modulated by an inhibitory T cell phenotype and modified dendritic cell (DC) phenotype in a gestation-dependent manner. We analyzed changes in surface markers of peripheral blood T cells, ex vivo antigen-specific T cell responses, indoleamine 2,3-dioxygenase (IDO) activity (kynurenine/tryptophan ratio, KTR), plasma neopterin concentration, and the in vitro expression of progesterone-induced blocking factor (PIBF) in response to peripheral blood mononuclear cell culture with progesterone. We found that mid gestation is characterized by reduced antigen-specific T cell responses associated with (1) predominance of effector memory over other T cell subsets; (2) upregulation of inhibitory markers (programmed death ligand 1); (3) heightened response to progesterone (PIBF); and (4) reduced proportions of myeloid DC and concurrent IDO activity (KTR). Conversely, antigen-specific T cell responses normalized in late pregnancy and were associated with increased markers of T cell activation (CD38, neopterin). However, these changes occur with a simultaneous upregulation of immune suppressive mechanisms including apoptosis (CD95), coinhibition (TIM-3), and immune regulation (IL-10) through the course of pregnancy. Together, our data suggest that immune tolerance dominates in the second trimester and that it is gradually reversed in the third trimester in association with immune activation as the end of pregnancy approaches.